2009
DOI: 10.5334/jpl.121
|View full text |Cite
|
Sign up to set email alerts
|

Wh-question intonation in Peninsular Spanish: Multiple contours and the effect of task type

Abstract: (cf. Cruttenden, 2007; but see also Lickley, Schepman, & Ladd, 2005). The experimental findings serve to clarify a number of assumptions about the syntax-prosody interface underlying wh-question utterance signaling; they also have implications for research methods in intonation and task-based variation in laboratory phonology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…This difference has been attributed to geographic variation and, more recently, to variation across tasks. Henriksen (2009) found evidence of style shifting for speakers from León, Spain, such that speakers were more likely to produce a final fall on an information gap mapping task than on a reading task, where the final rise was still widely attested. Likewise, this same type of variation across tasks was found for speakers of Manchego Spanish in Henriksen (2010), which provided a detailed account of how patterns changed across speakers and across tasks.…”
Section: Intonationmentioning
confidence: 93%
See 1 more Smart Citation
“…This difference has been attributed to geographic variation and, more recently, to variation across tasks. Henriksen (2009) found evidence of style shifting for speakers from León, Spain, such that speakers were more likely to produce a final fall on an information gap mapping task than on a reading task, where the final rise was still widely attested. Likewise, this same type of variation across tasks was found for speakers of Manchego Spanish in Henriksen (2010), which provided a detailed account of how patterns changed across speakers and across tasks.…”
Section: Intonationmentioning
confidence: 93%
“…Research on native intonation patterns for pronominal interrogatives has shown that although it may have once been thought that NSs produce final rises to signal this utterance type, there is actually considerable variation across studies (Face 2003, Henriksen 2009, O'Rourke 2005, Sosa 2003and Willis 2003. This difference has been attributed to geographic variation and, more recently, to variation across tasks.…”
Section: Intonationmentioning
confidence: 97%
“…For Peninsular Spanish, there is a history of research on the intonational patterns of speakers from the northern and central areas of Spain (e.g., Face 2002, Face 2008, Face 2011Prieto 2004;Estebas-Vilaplana and Prieto 2010), but the extent of intonational variation throughout the peninsula is not completely known. For Spanish generally, boundary falls are widely observed in wh-question intonation (Navarro Tomás 1944;Sosa 1999;Dorta Luis 2000;Sosa 2003;Prieto 2004;Henriksen 2009;Armstrong 2010; Willis 2010, among others), but detailed phonetic accounts with phonological implications are scarce. Prieto (2004) examined the speech data of two speakers from northern Spain and found that the most frequent contour contained a low-rise configuration (L*H%), although one speaker occasionally produced a contour comprised of a nuclear fall (H þ L* L%).…”
mentioning
confidence: 97%
“…These configurations occur in most varieties of Peninsular Spanish, documented for northern, central, and southern varieties (Prieto 2004;Henriksen 2009;Estebas-Vilaplana and Prieto 2010;López-Bobo and Cuevas-Alonso 2010;Henriksen and García-Amaya 2012;Henriksen 2013). The phonetic properties of the H þ L* and L þ ¡H* accents were examined in Henriksen (2014), where it was shown that the leading tones aligned within the last portion of the prestressed syllable and the starred tones aligned within the second half of the nuclear syllable.…”
mentioning
confidence: 98%
“…Most experimental work has focused on F0 movements in phrase-final position, due to their pragmatic, stylistic and regional variation (Estebas-Vilaplana and Prieto, 2010;Henriksen, 2009Henriksen, , 2013Henriksen, , 2014López-Bobo and Cuevas-Alonso, 2010;Prieto, 2004;Sosa, 1999). Navarro Tomás (1948), in his treatise on Spanish intonational structure, distinguishes 3 melodic contours used to signal wh-question intent, displayed in figure 2: a default falling contour (2a), a pragmatically motivated 'polite' contour characterized by a final rise (2b) and a circumflex contour characterized by a final rise-fall that communicates amazement or surprise (2c).…”
Section: Spanish Wh-question Intonationmentioning
confidence: 99%